ANALYZE SCIENTIFIC PRODUCTION AT THE FACULTY OF MEDICAL SCIENCES OF THE UNIVERSITY OF GUAYAQUIL - Daher, Jorge Nader; Panunzio, Amelia Patricia; Navarro, Marlene Hernández (International Journal of Research -GRANTHAALAYAH, 2020)
The results obtained in the analysis of the two sub-dimensions of the dimension are exposed: scientific production In general, the scientific production dimension addressed in the sub-dimensions scientific productivity and scientific results obtained a mean and SD of 2.38 ± 1,171 and 2.75 ± 1,386 respectively, classified as a medium level according to the opinion of the teachers, according to the scale used for such purposes.